Psalm twenty-three - Ladwig, Tim. (Grand Rapids : Eerdmans Books for Young Readers, 1997)
The text of the familiar psalm comparing God to a loving shepherd accompanies illustrations which shows the world of love and fear faced by an urban African-American family.
Originally published: New York : African American Family Press, c1993.
Keywords: Bible. -- Juvenile literature; Bible; African Americans -- Fiction; City and town life -- Fiction